Breastfeeding : Gender and Socio-Economic Dimensions - Yogi Pasca Pratama; Bhimo Rizky Samudro; Anang Pra Yogi (Universitas Muhammadiyah Ponorogo, 2018)
This study aims to examine breastfeeding behavior from a gender perspective and socio-economic dimension. The legal basis and internal and external factors of breastfeeding behavior are the main issues. Breastfeeding views are also studied in terms of working women, in response to the increasingly expensive economic needs of women to help the family economy by entering the labor market, while women also have an obligation to engage in breastfeeding activities. This study uses literature method, by collecting all the literature related to the breastfeeding process, the legal basis that supports, and the factors that can inhibit and the way to succeed exclusive breastfeeding issues. This study found the fact that there is a misconception of society about breastfeeding that the breastfeeding process is not optimal, the modernization also makes women who should breastfeed to make new choices instead of breastfeeding obligations for their children.